2017
DOI: 10.1038/srep45761
|View full text |Cite
|
Sign up to set email alerts
|

Structural heterogeneity of the μ-opioid receptor’s conformational ensemble in the apo state

Abstract: G-protein coupled receptors (GPCRs) are the largest and most pharmaceutically relevant family of membrane proteins. Here, fully unbiased, enhanced sampling simulations of a constitutively active mutant (CAM) of a class A GPCR, the μ-opioid receptor (μOR), demonstrates repeated transitions between the inactive (IS) and active-like (AS-L) states. The interconversion features typical activation/inactivation patterns involving established conformational rearrangements of conserved residues. By contrast, wild-type … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
20
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
1
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(21 citation statements)
references
References 56 publications
(81 reference statements)
1
20
0
Order By: Relevance
“…The receptor experienced numerous intermediate conformations along the deactivation pathway, but without a strong coupling mechanism between the orthosteric and G-protein-binding sites, giving a putative rationale for the experimental difficulties in fully stabilizing the β 2 -AR in the presence of an agonist [70]. In contrast, other MD studies have shown an allosteric communication between the orthosteric site and a conserved polar network of the μOR (opioid receptor μ) [71,72].…”
Section: Gpcr Activation and Signalingmentioning
confidence: 99%
“…The receptor experienced numerous intermediate conformations along the deactivation pathway, but without a strong coupling mechanism between the orthosteric and G-protein-binding sites, giving a putative rationale for the experimental difficulties in fully stabilizing the β 2 -AR in the presence of an agonist [70]. In contrast, other MD studies have shown an allosteric communication between the orthosteric site and a conserved polar network of the μOR (opioid receptor μ) [71,72].…”
Section: Gpcr Activation and Signalingmentioning
confidence: 99%
“…NPxxY is a highly conserved motif for class A GPCRs; it is located in the intercellular region of TM7 and is involved in the activation processes and modifications of | https://doi.org/10.1007/s42452-021-04505-8 a hydrophobic barrier [39]. Experimental data show that mutations in the NPxxY motif of β2AR or bradykinin B2 (B2R) affect coupling with G-proteins, exhibiting phosphorylation, and subsequent sequestration of these receptors [38,[40][41][42].…”
Section: Agonist and Allosteric Modulation Affect Conformations Around N332mentioning
confidence: 99%
“…However, detailed activation dynamics, especially the mechanism of functional selectivity, are difficult to capture by X-ray crystallography or cryoEM. NMR spectroscopy has proven to be particularly suitable for monitoring subtle dynamic conformational transitions during GPCR activation (Kofuku et al, 2014;Liang et al, 2018;Shimada et al, 2019). MD on the other side has provided insightful details of the potential activation processes (Latorraca et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…To this end, we have established a dual isotope labeling NMR scheme for µOR based on our previous study (Sounier et al, 2015). For the MD, we used the REST2 enhanced sampling scheme (REST2-MD), which has proven efficient in monitoring GPCR activation (Cong et al, 2019;Sena et al, 2017). We studied five chemically distinct µOR agonists ( Figure 1A): DAMGO, a well-characterized µORspecific peptide (Emmerson et al, 1994;Handa et al, 1981); buprenorphine, a semi-synthetic thebaine analogue and partial agonist (Cowan et al, 1977a;Cowan et al, 1977b); BU72, a potent buprenorphine derivative (Neilan et al, 2004); as well as the aforementioned selective agonists, TRV130 and PZM21.…”
Section: Introductionmentioning
confidence: 99%